2022
DOI: 10.1039/d2qi00816e
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic hybrid phosphite-participating S-shaped penta-CeIII-incorporated tellurotungstate as an electrochemical enzymatic hydrogen peroxide sensor for β-d-glucose detection

Abstract: Polyoxometalate chemistry has made rapid advances in innovative structural chemistry. The lower valence state and lone electron pair effect of subgroup-valence heteroatom Te(IV) can be introduced into the tungsten-oxygen system...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Polyoxometalates (POMs) are a large family of fascinating anionic metal oxide nanoclusters with excellent structure-dependent redox-active and charge-transfer properties, 23 making them attractive materials for significant applications as catalysts, 24 electrodes, 25 sensors, 26 and batteries. 27 Recently, many POM-based catalytic systems for oxidizing sulfides have been successfully established.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are a large family of fascinating anionic metal oxide nanoclusters with excellent structure-dependent redox-active and charge-transfer properties, 23 making them attractive materials for significant applications as catalysts, 24 electrodes, 25 sensors, 26 and batteries. 27 Recently, many POM-based catalytic systems for oxidizing sulfides have been successfully established.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that the Gibbs free energy of H* adsorption (Δ G H* ) is a crucial criterion to evaluate the activity of a hydrogen evolution electrocatalysts, and it is demonstrated that the smaller Δ G H* (|Δ G H* | ≈ 0) indicates better catalytic performance. As shown in Figure S13, combining the results of HOMO and LUMO electron densities for [Co 2 (TIB) 2 (PMo 12 O 40 )], four different types of oxygen atoms on Co-α-Keggin polymolybdate units represent four possible H* adsorption sites, namely, μ 3 -bridging oxygen (O a ), μ 3 -center oxygen (O c ), μ 2 -bridging oxygen (O b ), and terminal oxygen (O t ). According to the calculation results, μ 3 -bridging oxygen O a sites are the optimal adsorption site with a Δ G H* of −0.35 eV, which is lower than that of the O c site (0.28 eV), O b sites (0.32 eV), and O t sites (0.44 eV) . Particularly, the calculated Δ G H* values for the O a site is −0.11 eV, which is almost comparable to the Pt-based catalyst (|Δ G H* | ≈ 0.09 eV). , These results indicate that CoMo-POMOF and CoMo-POMOF nanopillar arrays indeed have great HER activity; meanwhile, also an important reason is that CoMo-POMOF and CoMo-POMOF nanopillar arrays possess higher electrochemical HER performance than other POMOF-base crystalline materials.…”
Section: Resultsmentioning
confidence: 67%
“…Water electrolysis for hydrogen production via the hydrogen evolution reaction (HER) is key in many electrochemical conversion technologies and energy conversion systems. , This promising and essential technology urgently needs low-cost and high-performance catalysts to improve energy conversion efficiency and reduce overpotentials. , Numerous efforts have been devoted to developing non-noble electrocatalysts, including Mo, Co, Fe, and Ni-based catalysts, to replace the precious-metal-based HER electrocatalysts. As special and exciting porous crystalline materials, POMOF combines the redox nature, stability, and diversity of the POM moiety , and the permanent porosity, readily accessible active sites, and well-defined chemical structures of MOFs, which may favor hydrogen evolution as an electrocatalyst. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a large surface-to-volume ratio guarantees them to possess highly exposed catalytic active sites . In addition, nanoenzymes can work as candidates for mimicking the catalytic process of bioenzymes and have demonstrated some incomparable advantages such as higher stability, lower cost, easier preparation, and so on. Currently, 2DMs as nanoenzyme catalysts are mainly based on graphene and its derivatives, transition-metal dichalcogenides, noble metals, etc., for applications of biosensing, environmental treatment, and nanodrugs. , Specially, Fe-based composite 2DMs can further promote nanoenzymatic performances because they can behave as a similar catalytic mechanism to the heme group of natural peroxidase. Therefore, Fe-based 2DMs may possess remarkable enzyme mimetic performance benefiting from synergistic effects of the favorable electron transfer capability of iron components and remarkable electronic attributes of 2DMs. However, intensive exploration on novel Fe-based 2DMs has been underdeveloped hitherto, and preparing nanoenzymatic Fe-based 2DMs and investigating their properties remain an enormous challenge.…”
Section: Introductionmentioning
confidence: 99%